Dielectric PMMA Thin Layers Obtained by Spin Coating for Electronic Applications - Elena Emanuela HERBEI (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2022)
Thin polymeric films with dielectric properties become a very important part of today’s devices, being indispensable in industry, electrical applications and not only. Nowadays polymeric materials have attracted attention in academic and industrial research due to the miniaturization at the micro and nanoscale of different electronic devices. Polymers in general are used for their light weight, good mechanical strength, dielectric properties, and optical properties, which make them multifunctional materials. This paper presents research on polymethyl methacrylate (PMMA) thin films obtained by the sol-gel method. The optimization of thin film PMMA layers has been a problem due to the importance of using the polymer in the different electronic domains. Thin films of PMMA with different thicknesses were deposited onto glass and silicon wafers in order to measure dielectric properties. For dielectric properties, the PMMA thin layer was inserted in a metal-insulator-metal structure (MIM). In order to observe the morphology and roughness of thin film, optical microscopy, scanning electron microscopy and atomic force microscopy have proceeded. The dielectric constant (k) was calculated using the electrical capacitance formula. The I-V and C-V curves showed a dielectric behavior with a leakage current between 10-11 and 10-8 A and a constant capacitance in the bias range ± 5 V.